Modeling of auditory neuropathy spectrum disorders associated with the TEME43 variant reveals impaired gap junction function of iPSC-derived glia-like support cells - Kang, Xiaoming; Ma, Lu; Wen, Jie; Gong, Wei; Liu, Xianlin; Hu, Yihan; Feng, Zhili; Jing, Qiancheng; Cai, Yuexiang; Li, Sijun; Cai, Xinzhang; Yuan, Kai; et al. (Frontiers in Molecular Neuroscience, 2025)
Auditory neuropathy spectrum disorder (ANSD) is an auditory dysfunction disorder characterized by impaired speech comprehension. Its etiology is complex and can be broadly categorized into genetic and non-genetic factors. TMEM43 mutation is identified as a causative factor in ANSD. While some studies have been conducted using animal models, its pathogenic mechanisms in humans remain unclear. TMEM43 is predominantly expressed in cochlear glia-like support cells (GLSs) and plays a vital role in gap junction intercellular communication. In this work, we utilized induced pluripotent stem cells from an ANSD patient carrying the TMEM43 gene mutation c.1114C>T (p.Arg372Ter) and directed their differentiation toward GLSs to investigate the effect of TMEM43 mutation on the function of gap junctions in cochlear GLSs in vitro. Reduced expression of genes associated with GLSs characteristics and reduced gap junction intercellular communication in TMEM43 mutant cell lines were observed compared to controls. Transcriptome analysis revealed that differentially expressed genes were significantly enriched in pathways related to cell proliferation, differentiation, extracellular space and adhesion. Furthermore, significant alterations were noted in the PI3K-Akt signaling pathway and the calcium signaling pathway, which could potentially influence gap junction function and contribute to hearing loss. In summary, our study based on patient-derived iPSCs sheds new light on the molecular mechanisms by which TMEM43 mutations may lead to ANSD. These mutations could result in developmental defects in GLSs and a diminished capacity for gap junction function, which may be implicated in the auditory deficits observed in ANSD patients. Our study explored the pathological effects of the TMEM43 mutation and its causal relationship with ANSD using a patient-derived iPSC-based GLSs model, providing a foundation for future mechanistic studies and potential drug screening efforts.